Early Life Adversity and Polygenic Risk for High Fasting Insulin Are Associated With Childhood Impulsivity - Batra, Aashita; Chen, Lawrence M.; Wang, Zihan; Parent, Carine; Pokhvisneva, Irina; Patel, Sachin; Levitan, Robert D.; Meaney, Michael J.; Silveira, Patricia Pelufo (Frontiers in Neuroscience, 2021)
While the co-morbidity between metabolic and psychiatric behaviors is well-established, the mechanisms are poorly understood, and exposure to early life adversity is a common developmental risk factor. Early life adversity (ELA) is associated with altered insulin sensitivity throughout life as well as with poor behavioral inhibition, which seems to contribute to the development of metabolic and psychiatric disturbances in the long term. We hypothesize that a genetic score associated with higher fasting insulin interacts with early life adversity to influence the development of executive functions (e.g. impulsivity in young children). We calculated polygenic risk scores (PRS) from the Fasting Insulin GWAS at different thresholds and identified the subset of single nucleotide polymorphisms (SNPs) that best predicted peripheral insulin levels in the ALSPAC cohort [N = 467; pt-initial = 0.24 (10,296 SNPs), pt-refined = 0.05 (57 SNPs)]. We then calculated the refined PRS (rPRS) for fasting insulin at these specific thresholds in the children from the MAVAN cohort and investigated its interaction effect with postnatal adversity on an impulsivity task applied at 36 months. We found a significant effect of interaction between fasting insulin rPRS and adversity exposure on impulsivity measured by the Snack Delay Task at 36 months [B = -650.6, p = 0.024], in which higher PRS [B = -0.551, p = 0.009] was linked to more impulsivity in individuals exposed to more adversity. Enrichment analysis (MetaCore) of the SNPs that compose the fasting insulin rPRS at this threshold was significant for certain nervous system development processes including dopamine D2 receptor signaling. Additional enrichment analysis (FUMA) of the genes mapped from the SNPs in the fasting insulin rPRS showed enrichment with the accelerated cognitive decline GWAS. The genetic background associated with risk for adult higher fasting insulin moderates the impact of early adversity on childhood impulsivity.